2001
DOI: 10.1103/physrevb.64.094506
|View full text |Cite
|
Sign up to set email alerts
|

Depairing currents in the superconductor/ferromagnet proximity system Nb/Fe

Abstract: We have investigated the behavior of the depairing current J dp in ferromagnet/superconductor/ferromagnet (F/S/F) trilayers as function of the thickness d s of the superconducting layers. Theoretically, J dp depends on the superconducting order parameter or the pair-density function, which is not homogeneous across the film due to the proximity effect. We use a proximity-effect model with two parameters ͑proximity strength and interface transparency͒, which can also describe the dependence of the superconducti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 25 publications
8
56
1
Order By: Relevance
“…This is not unexpected. In earlier work on the system Nb/ Fe, 16 we found that, in the Ginzburg-Landau ͑GL͒ regime close to T c , 27 J dp can be described as function of reduced temperature t = T / T c by the well-known expression J dp GL ͑t͒ = J dp GL ͑0͒͑1 − t͒ 3/2 , ͑1͒ also in the case that the order parameter is not constant over the thickness of the superconducting film. As a first step in the analysis, following Eq.…”
Section: Depairing Currentsmentioning
confidence: 90%
See 2 more Smart Citations
“…This is not unexpected. In earlier work on the system Nb/ Fe, 16 we found that, in the Ginzburg-Landau ͑GL͒ regime close to T c , 27 J dp can be described as function of reduced temperature t = T / T c by the well-known expression J dp GL ͑t͒ = J dp GL ͑0͒͑1 − t͒ 3/2 , ͑1͒ also in the case that the order parameter is not constant over the thickness of the superconducting film. As a first step in the analysis, following Eq.…”
Section: Depairing Currentsmentioning
confidence: 90%
“…21 The first issue requires samples with a bridge width w comparable with the penetration depth and the coherence length of the superconductor, respectively. Recent results 16,22 on Nb and MoGe single films and Fe/ Nb/ Fe trilayers, however, give us reason to expect uniform current distributions for w Ϸ 1.5 m. A classical pseudo-4-point geometry ͑meaning two contacts, each used for a current and a voltage lead͒ was defined using e-beam lithography. The structuring process, consisting of two main stages ͑e-beam writing and argon-ion etching͒, provided sharp-edged bridges.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the J dp is comparable with the J GL dp only at temperatures nearby the T c , but not at low-T, e.g. J dp (0)/J GL dp (0) ≈ 0.385 [21]. Thus, we get to the value J dp (0) ≈363.6 MA/cm 2 that is still a bit higher than the estimated one (≈ 200 MA/cm 2 [11]) but of the same order or magnitude.…”
Section: Fig 2 (Color Online)mentioning
confidence: 98%
“…For a tunnel barrier, it is given by I = I C sin(φ) as first found by Josephson [9], where I C is the critical Josephson current. When the two SCs coupled by a thin ferromagnetic layer [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], I C can change sign. Referring to the Josephson current-phase relationship, the change is corresponding to a π-phase shift of φ.…”
Section: Introductionmentioning
confidence: 99%